2015
DOI: 10.2175/106143015x14212658614838
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Biosorbent Lagenaria vulgaris Shell ‐ ZrO2 for the Removal of Textile Dye From Water

Abstract: A new biosorbent, abbreviated as LVB-ZrO₂, was synthesized by chemically modifying Lagenaria vulgaris shell with ZrO₂. The removal of textile dye RB19 from aqueous solution by LVB-ZrO₂was studied. Characterization by SEM, FTIR and XRD confirmed the chemical modification of the biomaterial, which showed significant improvement of removal efficiency compared with unmodified Lagenaria vulgaris shell. LVB-ZrO₂point of zero charge is 5.49. The biosorption process is highly pH dependent and the optimal pH is 2.0, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…This result contrasts those reported in previous articles [34], where the authors analyzed the optimal pH of the microalga Scenedesmus and identified pH 7.5 as optimal for discoloring the indigo blue. Petrović et al [50] reported an optimal pH of 2.0 for a new biosorbent, synthesized by chemically modifying Lagenaria vulgaris shell with ZrO 2 and abbreviated as LVB-ZrO 2 with blue textile dye RB19.…”
Section: Optimum Phmentioning
confidence: 99%
See 3 more Smart Citations
“…This result contrasts those reported in previous articles [34], where the authors analyzed the optimal pH of the microalga Scenedesmus and identified pH 7.5 as optimal for discoloring the indigo blue. Petrović et al [50] reported an optimal pH of 2.0 for a new biosorbent, synthesized by chemically modifying Lagenaria vulgaris shell with ZrO 2 and abbreviated as LVB-ZrO 2 with blue textile dye RB19.…”
Section: Optimum Phmentioning
confidence: 99%
“…The amount of absorbed dye as a function of time was measured for four different initial concentrations of indigo blue (25,50,75, and 100 mg/L) for 96 h. Figure 2 shows the observed experimental values (solid dots with error bars) and two fitted models for each initial concentration, where the dashed line is the first-order model in Equation 7and the solid line is the second-order rate model in Equation 8 [46]. Only one parameter was fitted to have more meaningful parameter values in all models [41,49,50]. For the first-order model, the fitted parameter was the adsorption rate, and the maximum adsorption (Qe) was fixed to 91% of the initial concentration (Ci) since we observed that the adsorption process reached equilibrium after three days and the amount of dye absorbed was consistently around an average of 91% of the initial concentration (C0) in all cases (Table 2).…”
Section: Measurement Of the Effect Of Time And Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recientemente se han estudiado como adsorbentes para la remoción de colorantes en agua Lagenaria vulgaris (Petrović, Radović, Kostić, Mitrović, Bojić, Zarubica & Bojić, 2015), planta trepadora conocida comúnmente como calabaza de peregrino (figura 4a), y Mucuna pruniens (Igwegbe, Onyechi, Onukwuli & Nwokedi, 2016), leguminosa conocida con el nombre común de grano de terciopelo (figura 4b). L. vulgaris fue modificado químicamente empleando óxido de zirconio, lo cual dio como resultado un nuevo biomaterial adsorbente denominado LVZrO 2 , que removió de forma eficiente el colorante textil RB19.…”
Section: Adsorbentes Naturalesunclassified